Shakespeare Made Easy: A Midsummer Night's Dream - Durband, Alan (Stanley Thornes (Publishers) Ltd, 1989)
Shakespeare Made Easy is intended for readers approaching the plays for the first time, who find the language of Elizabethan poetic drama an initial obstacle to understanding and enjoyment. Now you can instantly grasp the rich commedy and magical enchantment of Shakespeare's best-loved play. This famous story of spirits and spell, tricks and potions, lovers lost and found, and a perfect happy ending, unfolds in clear, modern English.
Keywords: Drama; Drama; Juvenile Literature